TOBACCO PRODUCTS STOCK MANAGEMENT ON THE CASE OF THE RETAIL CHAIN IN THE REPUBLIC OF SERBIA - Tekic, Tanja; Tekic, Dragana (Journal of process management and new technologies, 2018)
Companies nowadays have profit as a main goal with optimal costs and other resources. However, how to achieve the optimal costs and resources are the main issue and problem for all companies? Is the way to achieve them the same for all organizations, industries? Off course not, every company organize its business in accordance to the environment and internal needs. This paper are based on tobacco products stocks analysis, data are collected for the retailer operating in the urban, city area in Serbia. In order to complement analysis stock level data for observed tobacco product used in paper, temperature and retail sales data have been collected. Mentioned data collection, analysis and research were implemented in order to set up an adequate model which should be used in the retailer future projections of the stock level and optimization of the costs.